Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/mnras/stu2010
|View full text |Cite
|
Sign up to set email alerts
|

Chandra survey in the AKARI North Ecliptic Pole Deep Field – I. X-ray data, point-like source catalogue, sensitivity maps, and number counts

Abstract: We present data products from the 300 ks Chandra survey in the AKARI North Ecliptic Pole (NEP) deep field. This field has a unique set of 9-band infrared photometry covering 2-24 µm from the AKARI Infrared Camera, including mid-infrared (MIR) bands not covered by Spitzer. The survey is one of the deepest ever achieved at ∼15 µm, and is by far the widest among those with similar depths in the MIR. This makes this field unique for the MIR-selection of AGN at z ∼ 1.We design a source detection procedure, which pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 44 publications
1
67
0
Order By: Relevance
“…CMLDetect has been adapted to run on Chandra data by replacing the XMM-Newton PSF library with the Chandra one (see Krumpe et al 2015 for another application of CMLDetect). Moreover, this new tool can also work with different PSFs simultaneously.…”
Section: Data Analysis: Source Detection and Photometrymentioning
confidence: 99%
“…CMLDetect has been adapted to run on Chandra data by replacing the XMM-Newton PSF library with the Chandra one (see Krumpe et al 2015 for another application of CMLDetect). Moreover, this new tool can also work with different PSFs simultaneously.…”
Section: Data Analysis: Source Detection and Photometrymentioning
confidence: 99%
“…Hanami et al (2012) showed that the rest-frame 8 µm and 5 µm luminosities are good tracers of star-forming and AGN activities from their Polycyclic Aromatic Hydrocarbons (PAH) and dusty tori emissions, respectively. As for the AGN dominated MIR-selected sources (inferred from their MIR SEDs), Krumpe et al (2014) found a high (∼ 40%) X-ray detection rate, while sources without any sign of AGN activity in their MIR SEDs have a very low X-ray detection rate of 3%. They also concluded that roughly 30% of IR-selected AGN are strong Comptonthick AGN candidates; this is about to be verified by rest-frame X-ray stacking (Miyaji et al in prep.).…”
Section: Recent Scientific Progressmentioning
confidence: 84%
“…As for the optical-NIR data, new band-merged catalogue (u * , g , r , i , z , Y , J, K s ) was generated from (Oi et al, 2014). The 300 ks Chandra X-ray image data are also published in Krumpe et al (2014).…”
Section: Recent Progress In Multiwavelength Datamentioning
confidence: 99%
“…The NEP (centered at R.A. = 18 h 00 m 00 s , decl.= 66 d 33 m 38 552) is the natural extragalactic deep field and has one of the deepest observations by several space observatories, including Planck and AKARI (Serjeant et al 2012). Furthermore, it has extensive observations from the X-ray to the millimeter (Kollgaard et al 1994;Gioia et al 2003;Lee et al 2007;Jeon et al 2010Jeon et al , 2014Krumpe et al 2015), with additional observations by WISE (Jarrett et al 2011). The field was specifically chosen to match the observations by the Cosmic Infrared Background Experiment (CIBER; Bock et al 2013;Zemcov et al 2014 as per msp) to study the extragalactic background light fluctuation (Cooray et al 2004(Cooray et al , 2012aMatsumoto et al 2005;Zemcov et al 2014;Matsuura et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Spitzer infrared observations in the NEP could additionally be utilized (in conjunction with the already existing X-ray observations; Krumpe et al 2015) to identify AGNs (Stern et al 2005). The NEP imaging data are particularly important for studies of diffuse light background fluctuations arising from individually undetected sources directly probing early star formation (Cooray et al 2004(Cooray et al , 2012aZemcov et al 2014).…”
Section: Introductionmentioning
confidence: 99%